Labor market participation: The impact of social benefits in the Czech Republic - Kamila Fialová; Martina Mysíková (Charles University in Prague, Institute of Economic Studies (IES), 2009)
This paper aims to quantify the impact of social benefits on labor market participation in the Czech Republic. It applies the logistic regression to estimate the probability of labor market participation depending on social benefits related to net wage of the individuals, controlling for individual and household characteristics (age, presence of spouse and children etc.). The work disincentives via social benefits do exist and proved to be relatively strong. When trying to understand the reasons for recently decreasing participation rate in the Czech Republic, the often called generous Czech social benefit system appears to be relevant.
Keywords: I38; J21; 330; inactivity trap; labor market participation; social benefits; Soziale Sicherung; Erwerbstätigkeit; Ökonomischer Anreiz; Tschechische Republik